Treatment of Severe Keratoconus Hydrops With Intracameral Platelet-Rich Plasma Injection. Issue 12 (December 2019) - Alio, Jorge L.; Toprak, Ibrahim; Rodriguez, Alejandra E.
Abstract : Purpose: To present successful management of severe corneal hydrops by corneal optical coherence tomography (OCT) guidance and intracameral application of eye platelet-rich plasma (E-PRP) in a case with Down syndrome. Methods: A 36-year-old woman with Down syndrome presented with acute vision loss, pain, photophobia, and corneal edema in the left eye. Clinical examination revealed keratoconus in the right eye and extreme keratoconus with severe corneal hydrops in the left eye. Anterior segment OCT (MS-39, Costruzione Strumenti Oftalmici, Firenze, Italy) showed intrastromal cystic fluid collection and ruptured and detached Descemet membrane. The OCT-guided management of hydrops is first described in this case report. Results: Medical treatment and intracameral sulfur hexafluoride injection failed. A sterile 0.3 mL of E-PRP was injected into the anterior chamber. Clinical and anatomical improvement began from the first postoperative day, and corneal edema totally resolved at 1 week. Postoperatively, no significant side effect was noted except an early transient moderate (28 mm Hg) intraocular pressure peak. Anterior segment-OCT demonstrated dramatic normalization in corneal morphology with total disappearance of fluid in the cystic intracorneal space, closure of the DM rupture, and DM reattachment. The patient was stable during the 6-month follow-up. Conclusions: In this case, intraocular E-PRP was a promising, apparently safe, and effective treatment option in management of corneal hydrops, in which conventional approaches failed. This is the first case in the literature to describe OCT appearance of corneal hydrops and intracameral use of E-PRP for the resolution of DM rupture in acute corneal hydrops.